S59 Using venous blood gas analysis in the management of COPD exacerbations; a prospective cohort study. (12th November 2015) - Shaw, DE; Kelly, AM; Housley, G; Hearson, G; Reynolds, C; Harrison, TW; McKeever, TM
Abstract : Introduction: COPD exacerbations are a common cause of emergency hospital admission in the UK, with an estimated 94, 000 per year. Identifying hypercapnic respiratory failure is crucial. Guidelines recommend obtaining arterial blood samples but these are more difficult to obtain than venous samples. Furthermore, administration of local anaesthetic prior to arterial sampling is seldom used. We assessed whether blood gas values derived from venous samples could replace arterial at initial assessment. Methods: Patients treated for a COPD exacerbation had paired arterial and venous samples taken. Bland Altman analyses were performed to assess agreement between arterial and venous pH, PCO2 and HCO3 -, and between SpO2 and SaO2 . The number of attempts and pain scores for each sample were measured. Results: 234 patients had paired arterial and venous samples. There was good agreement between arterial and venous measures of pH and HCO3 - (mean difference 0.03 and -0.04, limits of agreement -0.54 to 0.11, and -2.90 to 2.82), and between SaO2 and SpO2 (in patients with a SpO2 of greater than 80%). We calculated the sensitivity and specificity of a VBG pH and HCO3 - to correctly identify an arterial pH of ≥7.35, and an arterial HCO3 - of ≥21, as well as a SpO2 to identify a SaO2 of ≥ 92%. A venous pH of 7.34, a venous HCO3 - of 21.45 and a SpO2 of 91.5 would have correctly classified 87% (95% CI 82% to 91%), 97% (95% CI 93% to 98%), and 71% (95% CI 65% to 77%), of patients respectively. 96% of patients with an ABG pH of ≥7.35 also had a VBG pH of ≥7.35. Arterial sampling took more attempts and was more painful than venous (mean pain score 4 (IQR 2–5) and 1 (IQR 0–2), p < 0.001). Conclusion: Arterial sampling is more difficult and painful than venous sampling. There is good agreement between pH and HCO3 - values derived from venous and arterial blood, and between pulse oximetry and arterial blood gas oxygen saturations. This could allow the initial assessment of COPD exacerbations to be based on venous blood gas analysis and pulse oximetry, simplifying the care pathway and improving the patient experience.